In need of a master: politics, theology, and radical democracy - Finkelde, Dominik; Klein, Rebekka A. (De Gruyter, 2021)
Frontmatter -- Table of Contents -- Introduction: Political Theologies in the Era of Immanence -- I Figurations of the Master -- Sklaven ohne Herrn -- Sovereignty Figures in the History of the ‘Finance Regime’ -- Im Namen des Vaters -- Spinoza on the Death of the Master -- Enmity as Cast Shadow of Love -- Meister, Väter und Surrogate -- II Identity – Diversity – Singularity -- Cis: The Rightist Appropriation of Identity Politics and its Boundaries -- In Need of A Master -- The Sovereignty of Subversion -- Total Fidelity? -- III Post-Political Theology -- Das Relative als das Absolute? -- Theopolitics Today -- Smashing Words -- On the Abuses and Uses of Political Theology -- List of contributors -- Index